Postoperative healing after surgical removal of mandibular third molar: A comparative study between two proteolytic enzymes - S Tharani Kumar; R Ashok Prasanna; Joshua Rohan Kirubanandan; U Elaveyini; S Prasanna Devi; Murali Balasubramaniam (Wolters Kluwer Medknow Publications, 2020)
Objective: The postoperative symptoms after third molar removal surgery were commonly uneventful. The aim of this study was to compare two proteolytic enzymes from different origin and to prove which enzyme provides a faster healing. One of the proteolytic enzymes involves a combination with a flavonoid. This involves trypsin, bromelain, along with a flavonoid rutin. Another proteolytic enzyme is serratiopeptidase that helps in degradation of insoluble proteins causing reduced swelling in the operated site. Materials and Methods: In this study, voluntary subjects of clinically indicated bilateral lower third impaction were selected. The subjects were recommended to undergo extraction of impacted teeth in two sittings, one extraction per visit. In the first sitting, subjects were prescribed trypsin, bromelain, and rutin combination after removal of 48 teeth and in the second sitting subjects were prescribed serratiopeptidase after removal of 38 teeth. There was a time interval of 2-3 weeks in between the sittings. The post findings such as mouth opening, swelling, and pain scale were noted. Results: The results showed that the proteolytic enzyme combination of trypsin, bromelain, and rutin is better than serratiopeptidase. Conclusion: It is recommended that trypsin, bromelain, and rutin combination can be used effectively for postoperative purpose to facilitate wound healing.